PENGARUH BIAYA DISTRIBUSI DAN HARGA PRODUK TERHADAP VOLUME PENJUALAN EKSPOR PADA PUPUK ORGANIK SAN 500 gr (Studi Kasus Pada PT. Indmira Yogyakarta) - Suryo Adi Prasojo; Andi Setiawan; Sri Wahyuni (JOBS (Jurnal Of Business Studies), 2017)
PT Indmira Yogyakarta has two products to export, they are SAN and SNN. The two exported products of PT. Indmira have direfferent export sales volumes, SAN had fewer export sales volume than SNN, therefore the writer observed the reasons why this problem could happen by using variables which influenced export sales volume. The variables are distribution cost and product price. PT. Indmira Yogyakarta is one of organic fertilizer producer companies in Indonesia. The aim of this research is to identify the influence of distribution cost and product price toward SAN organic fertilizer 500 gr export sales volume at PT. Indmira Yogyakarta. This research used coeffcient determination, F test, t test and multiple linear regression as the analyzing methods. The data used in this research are distribution cost data, product price data and SAN organic fertilizer 500 gr export sales volume data from 2012-2016 at PT. Indmira Yogyakarta. This research finds that the distribution cost and product price influences the export sales volume stimultaneously, and partially distribution cost does not have significant influence while the product price have significant influence toward the export sales volume. The distribution cost and product price influence the export sales  volume by 20%. The dominant variable in this research is product price. Since the product price becomes the dominant variable in this research, therefore PT. Indmira should consider the price determination for its products.  The conclusion of this research is the distribution cost and product price has significant influence towards the export sales volume stimultaneously, and partially the distribution cost does not have significant influence toward the export sales volume while the product price has significant influence toward the export sales volume. The distribution cost and product price influence the export sales volume by 20%, and the dominant variable is product price. Since this research only used two variables, this could be the weakness of the research. Therefore, it is suggested for the next research to use different variables other than the variables in this research which influence the export sales volume by 80%.